Enhancing salt leaching efficiency of saline-sodic coastal soil by rice straw and gypsum amendments in Jiangsu coastal area - Khailah Ebrahim Yahya; Zhonghua Jia; Wan Luo; He YuanChun; Michael Aliyi Ame (Ain Shams Engineering Journal, 2022)
High salinity-sodicity affects large areas of newly-reclaimed land in many coastal regions that need proper leaching before they become productive. However, poor soil properties make salt-leaching process ineffective. In this study, leaching experiments were used to assess the effectiveness of adding gypsum and rice straw in improving salt-leaching efficiency. Four treatments, control, rice-straw, gypsum, and gypsum and rice-straw, with two replicates, each were tested to find the optimal combination. After soils were leached, property changes were measured, such as main dissolved cations, conductivity, and pH. Gypsum and rice straw treatment turned out to be the best, where ECe, sodium adsorption ratio, and exchangeable sodium percentage dropped to 3.61%, 5.04%, and 8.14%, respectively. These values reached the safe limit of salinity-sodicity (ECe ≤ 4dS m−1, ESP ≤ 15%). In addition, the incorporation of rice-straw with gypsum affects the ability to increase the removal of sodium and thus enhance salt-leaching efficiency.